2006
DOI: 10.1038/sj.tpj.6500428
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic–gene interaction and the risk of myocardial infarction and stroke

Abstract: This study investigates whether the interaction between diuretics and alphaadducin (ADD1) G460W or G-protein b3-subunit (GNB3) rs2301339 polymorphism modifies the risk of myocardial infarction (MI) or stroke. Data were used from the Rotterdam Study. The drug-gene interaction was determined with a Cox proportional hazard model with adjustment for each drug class as time-dependent covariates. The risk of MI in current users of low-ceiling diuretics with one or two copies of the ADD1 W-allele (hazard ration (HR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The ADD1 variant rs4961 has been studied extensively on its own. However, results have been conflicting as the T allele has been found to confer increased diuretic efficacy in some studies, but reduced efficacy in others 42,[75][76][77][78][79][80][81][82][83][84] .…”
Section: Candidate Variants Contributing To Sodium Reabsorptionmentioning
confidence: 99%
“…The ADD1 variant rs4961 has been studied extensively on its own. However, results have been conflicting as the T allele has been found to confer increased diuretic efficacy in some studies, but reduced efficacy in others 42,[75][76][77][78][79][80][81][82][83][84] .…”
Section: Candidate Variants Contributing To Sodium Reabsorptionmentioning
confidence: 99%
“…Three studies [8,15,16] showed a greater BP response to hydrochlorothiazide among carriers of the Trp allele. In three studies, one performed in nonHispanic black and non-Hispanic white patients in the USA, and two in observational cohort studies in the Netherlands among whites, no relationship between the a-adducin genotypes and BP response to diuretics was found [17][18][19].…”
Section: Introductionmentioning
confidence: 96%
“…The variation of response in preventing MI and stroke has been assessed in four studies [19][20][21][22] until now. The results of these studies are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified associations between C825T polymorphism (rs5443), rs2301339, and rs5446 of the GNB3 gene with hypertension, myocardial infarction, stroke or type 2 diabetes [8,9,13,[25][26][27]. However, no studies have examined association between these three genetic variants of the GNB3 gene and BP response to potassium-implementation.…”
Section: Discussionmentioning
confidence: 99%